Chrześcijański argument „z sensu życia i świata” wobec buddyjskiego poglądu na rzeczywistość - Andrzej Persidok (Warszawskie Studia Teologiczne)
The starting point of the article is the „argument from meaning” used in fundamental theology. The authors referring to it argue that only religion can give meaning to human life and the world. A man who does not want to run away from ultimate questions is faced with an alternative: faith in God or nihilism. Among religions, however, there is one that rejects belief in God and in any transcendence, and yet claims to be a source of meaning in life for its adepts. This religion is Buddhism. In this study, an attempt was made to confront the theological argumentation "from the meaning of life and the world" with the Buddhist worldview. The aim of such a confrontation is to locate potential weak points of this type of argumentation, which can help refine it so that it is also convincing for people outside Western culture.